Prognostic Values of Three Equations in Estimating Glomerular Filtration Rates of Patients Undergoing Off-Pump Coronary Artery Bypass Grafting - Li Z; Ge W; Han C; Lv M; He Y; Su J; Liu B; Zhang Y (Dove Medical Press, 2020)
Zhi Li,1,* Wen Ge,2,* Chunyan Han,3,* Mengwei Lv,4,5,* Yanzhong He,5 Juntao Su,6 Ban Liu,3 Yangyang Zhang5 1Department of Cardiovascular Surgery, Jiangsu Province Hospital, The First Affiliated Hospital of Nanjing Medical University, Nanjing, People’s Republic of China; 2Department of Thoracic and Cardiovascular Surgery, Shuguang Hospital, Shanghai University of TCM, Shanghai, People’s Republic of China; 3Department of Cardiology, Shanghai Tenth People’s Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China; 4Shanghai East Hospital of Clinical Medicine College, Nanjing Medical University, Shanghai, People’s Republic of China; 5Department of Cardiovascular Surgery, Shanghai East Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China; 6Tongji University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yangyang Zhang; Ban Liu Email zhangyangyang_wy@tongji.edu.cn; 2013liuban@tongji.edu.cnBackground: Renal dysfunction is independently associated with both short-term and long-term mortality after coronary artery bypass grafting (CABG). The estimated glomerular filtration rate (eGFR) is a convenient and effective indicator of renal function. However, the ability of eGFR calculated by various equations to predict the outcomes of patients undergoing off-pump CABG (OPCABG) is still unclear. This study was aimed to compare the predictive ability of in-hospital and long-term mortality in three equations of estimating renal functions after OPCABG.Methods: Totally, 1362 patients undergoing OPCABG were retrospectively reviewed. Preoperative and postoperative serum creatinine (Scr) levels were detected. The renal function was evaluated by the Cockcroft-Gault (CG) equation, the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation, and the full-age spectrum (FAS) equation. The endpoints were in-hospital and long-term all-cause mortality rates. Receiver operating characteristic curves, net reclassification index, decision curve analysis (DCA), multivariable logistic model, and Cox regression model were used for comparisons.Results: The CG equation had the significantly highest discriminatory power to predict in-hospital mortality (area under the curve=0.815). Valuable clinical net benefits of the CG equation were greater than the other two equations regardless of before or after operation by DCA. Multivariable logistic and Cox regression analysis illustrated that the eGFR calculated by the CG equation was a significant independent risk factor of both in-hospital mortality (odds ratio=3.390) and long-term mortality (hazard ratio=1.553).Conclusion: The CG equation outperformed the FAS and CKD-EPI equations in predicting the mortality of patients after OPCABG. Postoperative renal function was more efficiently predicted compared with the preoperative one.Keywords: coronary artery bypass grafting, off-pump, estimated glomerular filtration rate, mortality